2019
DOI: 10.9734/irjpac/2019/v19i330109
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Amlodipine Besilate and Azilsartan Medoxomil by UHPLC, HPTLC and Spectrophotometric Techniques

Abstract: Aims: To develop methods with complete validation according to ICH guidelines and to be applied for the determination of both drugs in laboratory prepared mixtures and in synthetic tablets. Study Design:  Ultra high performance liquid chromatography (UHPLC), High performance thin layer chromatography (HPTLC) and visible spectrophotometric methods are developed for determination of amlodipine besilate and azilsartan medoxomil in laboratory-prepared mixtures and in synthetic tablets. Methodology: Two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…3 It is reported officially in Indian Pharmacopoeia (IP)-2018. 4 Literature study revealed that the analytical techniques like HPTLC, [5][6] HPLC, [7][8] UVspectrophotometry, 9,10 LC/MS-MS [11][12] methods have been presented for determination of Azilsartan medoxomil and Cilnidipine as a single, while for the combination of Azilsartan medoxomil and Cilnidipine method is available on UV-spectroscopy 13 and HPLC, 14 there is no article related to Stability Indicating HPLC Assay method to quantify Azilsartan medoxomil and Cilnidipine in bulk has ever been mentioned within literature referred. The primary goal of this project was to produce a specific, accurate, and reproducible stability indicating HPLC methods for determination of Azilsartan medoxomil and Cilnidipine as stated in the ICH guidelines.…”
Section: Introductionmentioning
confidence: 99%
“…3 It is reported officially in Indian Pharmacopoeia (IP)-2018. 4 Literature study revealed that the analytical techniques like HPTLC, [5][6] HPLC, [7][8] UVspectrophotometry, 9,10 LC/MS-MS [11][12] methods have been presented for determination of Azilsartan medoxomil and Cilnidipine as a single, while for the combination of Azilsartan medoxomil and Cilnidipine method is available on UV-spectroscopy 13 and HPLC, 14 there is no article related to Stability Indicating HPLC Assay method to quantify Azilsartan medoxomil and Cilnidipine in bulk has ever been mentioned within literature referred. The primary goal of this project was to produce a specific, accurate, and reproducible stability indicating HPLC methods for determination of Azilsartan medoxomil and Cilnidipine as stated in the ICH guidelines.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous analytical techniques have been established for the determination of CEL and AMLO alone or combined with other drugs as spectrophotometric [8][9][10][11], spectrofluorometric [12][13][14][15], high-performance thin-layer chromatography (HPTLC) [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30], HPLC [31][32][33], and electrochemical methods [34,35]. A few recently analytical techniques have been established for the simultaneous estimation of CEL and AMLO such as spectrophotometric [36], spectrofluorimetric [37], and HPLC [38,39].…”
Section: Introductionmentioning
confidence: 99%
“…The literature review on the availability of analytical methods for Azilsartan revealed a UV spectroscopic method, 7 few ultra-performance liquid chromatographic method and LC-MS methods for the quantification of Azilsartan in bulk drug, plasma 8,9 and combination with other drugs 10,11 and stability-indicating high-performance thin layer chromatographic (HPTLC) method. 12 In the literature survey, many chromatographic analytical methods were developed having several drawbacks include high buffer concentration leads to column damage, time-consuming and tedious. It needs to develop a method that resolves the problems of the previous methods.…”
Section: Introductionmentioning
confidence: 99%